Numerical simulation and performance evaluation of skin friction reduction by boundary layer injection under hypervelocity inflow condition - Zhenming Qu; Feiteng Luo; Yaosong Long; Wenjuan Chen (Propulsion and Power Research)
This study proposes a quantitative evaluation framework to assess the performance of boundary layer injection (BLI) technology, establishing standardized metrics for integration into performance analysis of scramjets. We comparatively evaluate inert gas and fuel BLI strategies under typical combustor inflow conditions through systematic numerical investigations employing this evaluation framework. Key findings reveal that fuel injection demonstrates superior skin friction reduction efficacy compared to inert gases, especially hydrogen, achieving skin friction reduction performance up to 600 s at Mach 8+ conditions with an injection equivalence ratio (ER) of 0.1. Hydrogen's advantage arises from its inherently low density, coupled with combustion-induced density reduction in the log-law region. This dual mechanism suppresses turbulent momentum transport and attenuates skin friction through large-scale flow restructuring. However, when benchmarked against reacting mainstream flows without BLI, fuel injection efficacy diminishes significantly (100 s level) — local density reduction effects induced by boundary layer combustion are attenuated by mainstream heat release, limiting further momentum transport suppression and reducing drag reduction performance to inert gas levels. These results underscore the critical influence of ambient combustion conditions on BLI effectiveness, emphasizing that BLI implementation must prioritize non-reacting or weakly reacting flow environments. The proposed standardized metrics address this operational dependency, enabling BLI optimization within full-engine design paradigms to prevent counterproductive “pseudo-optimization.''